2003
DOI: 10.1086/378125
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis and the Respiratory System

Abstract: Brucellosis is a zoonotic disease that remains endemic worldwide. Its clinical manifestations and focal complications are often troublesome in making a diagnosis. Involvement of the respiratory system in brucellosis is an acknowledged but rare event that is only occasionally described in literature. We describe 37 cases of respiratory involvement during the course of brucellosis that presented as pneumonia, bronchopneumonia, pleural effusion with a predominance of monocytic or lymphocytic infiltrates, and paro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 17 publications
5
91
1
2
Order By: Relevance
“…[41][42][43]49,50 Several studies have identified patients with pulmonary brucellosis and pleural effusions. [51][52][53][54][55] Although we identified 1 (11.1%) patient with brucellosis and pleural effusion, it was not a consistent finding in our cohort.…”
Section: Discussionmentioning
confidence: 75%
“…[41][42][43]49,50 Several studies have identified patients with pulmonary brucellosis and pleural effusions. [51][52][53][54][55] Although we identified 1 (11.1%) patient with brucellosis and pleural effusion, it was not a consistent finding in our cohort.…”
Section: Discussionmentioning
confidence: 75%
“…Endocarditis was confirmed by auscultation of a cardiac murmur and detection of valvular vegetations using trans-thoracic echocardiography (15). Respiratory complications were defined by the protocol described by Pappas et al (16).…”
Section: Methodsmentioning
confidence: 99%
“…Brucellosis can lead to the compromise of the peripheral nervous system, leading to radiculopathy 14 . Lung diseases are common after inhalation of aerosols with Brucella 15 . The inhalation occurs during manipulation of cultures or clinical samples containing bacteria.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…The inhalation occurs during manipulation of cultures or clinical samples containing bacteria. Interstitial pneumonitis, pneumonia, bronchopneumonia, pleural effusion, and lung nodules are conditions related to Brucella infection 15 .…”
Section: Clinical Findingsmentioning
confidence: 99%